Improvement of central vein ultrasound-guided puncture success using a homemade needle guide—a simulation study - Antoine Villa; Vladimir Hermand; Vincent Bonny; Gabriel Preda; Tomas Urbina; Maxime Gasperment; Paul Gabarre; Louai Missri; Jean-Luc Baudel; Daniel Zafimahazo; Jérémie Joffre; Hafid Ait-Oufella; et al. (Critical Care, 2023)
Abstract Background Out-of-plane (OOP) approach is frequently used for ultrasound-guided insertion of central venous catheter (CVC) owing to its simplicity but does not avoid mechanical complication. In-plane (IP) approach might improve safety of insertion; however, it is less easy to master. We assessed, a homemade needle guide device aimed to improve CVC insertion using IP approach. Method We evaluated in a randomized simulation trial, the impact of a homemade needle guide on internal jugular, subclavian and femoral vein puncture, using three approaches: out-of-plane free hand (OOP-FH), in-plane free hand (IP-FH), and in-plane needle guided (IP-NG). Success at first pass, the number of needle redirections and arterial punctures was recorded. Time elapsed (i) from skin contact to first skin puncture, (ii) from skin puncture to successful venous puncture and (iii) from skin contact to venous return were measured. Results Thirty operators performed 270 punctures. IP-NG approach resulted in high success rate at first pass (jugular: 80%, subclavian: 95% and femoral: 100%) which was higher than success rate observed with OOP-FH and IP-FH regardless of the site (p = .01). Compared to IP-FH and OOP-FH, the IP-NG approach decreased the number of needle redirections at each site (p = .009) and arterial punctures (p = .001). Compared to IP-FH, the IP-NG approach decreased the total procedure duration for puncture at each site. Conclusion In this simulation study, IP approach using a homemade needle guide for ultrasound-guided central vein puncture improved success rate at first pass, reduced the number of punctures/redirections and shortened the procedure duration compared to OOP and IP free-hand approaches.